PELAKSANAAN AUDIT INTERNAL DALAM MEWUJUDKAN GOOD CORPORATE GOVERNANCE PADA SEKTOR PUBLIK - PUGUH NUGROHO, DHIMAS Puguh (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this study is to know how the implementation of internal audit in achievinggood corporate governance in the public sector. The results showed that the implementationof internal audit in accordance with auditing standards and in accordance with the stages ofthe audit, it can increase transparency and accountability principles on good corporategovernance. Thus indicating the existence of significant influence in achieving goodcorporate governance in the public sector, which means that if an internal audit carried outwell, then good corporate governance is also performing well.Keywords: Internal audit, Good corporate governace